Diversity and use medicinal plants for traditional women’s health care in Kalibawang, Wonosobo District, Indonesia (Asian Journal of Ethnobiology, 2025)
Abstract. Nuraini A, Rabbani AH, Jagatru AS, Azzahra AN, Azizia MS, Yasa A, Saensouk S, Setyawan AD. 2023. Diversity and use medicinal plants for traditional women’s health care in Kalibawang, Wonosobo District, Indonesia. Asian J Ethnobiol 7: 145-155. Indonesia, known as a country with "mega-biodiversity" and cultural diversity, has large and diverse natural resources, including medicinal plants that have not been fully explored. These medicinal plants play an important role in primary health care, as well as for women health care in various ethnics across the country. This study aims to determine the plants used for women's health in Kalibawang Sub-district, Wonosobo District, Central Java, Indonesia, with a focus on menstruation, pregnancy, lactation, and postpartum recovery. The research methods include interviews with 106 people who have knowledge of medicinal plants and field observations. The results of the study identified 33 plant species from 17 families for women health care, with the Zingiberaceae family as the mostly used. Plants such as kunyit (Curcuma longa), jahe (Zingiber officinale), katuk (Sauropus androgynus), and sirih (Piper betle) have an important role in women's reproductive health. Curcuma longa ranked highest in SUV (0.557) and RFC (0.038), with a Fidelity Level (FL) of 100%, reflecting consistent use for specific purposes. The study also found that medicinal plants not only provide physical health benefits, but also significant cultural and spiritual values ??for local communities.
Keywords: Health, mega-biodiversity, traditional medicine, women